PENGARUH STRATEGI PEMBELAJARAN KOOPERATIF TIPE COOPERATIVE SCRIPT DAN STRATEGI PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP DAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS XI PADA MATERI PROGRAM LINEAR SMA NEGERI 1 TANJUNG PURA T.P 2018-2019 - Nadhira Nadhira; Isran Rasyid Karo Karo S (AXIOM : Jurnal Pendidikan dan Matematika, 2019)
This study aims to: 1) know that the ability of students to understand the concepts taught by the Cooperative Script Strategy is more influential than to be taught with the Problem Based Learning Strategy; 2) knowing that students' mathematical problem solving abilities taught by Cooperative Script Strategies are more influential than being taught with Problem Based Learning Strategies; 3) knowing that the ability of understanding concepts and mathematical problem solving taught by Cooperative Script Strategies is more influential than being taught with Problem Based Learning Strategies. 4) knowing the interaction between learning strategies on the ability to understand concepts and students' mathematical problem solving abilities. This research is a type of quantitative research with a quasi-experimental approach. The population is all students of class XI IPA of SMA Negeri 1 Tanjung Pura T.P 2018-2019 consisting of 3 classes and totaling 104 students will be selected 2 classes as the experimental class and the control class that are sampled in this study. The test instrument used by using a test in the form of description. Data analysis was performed using Two Path Analysis of Variance (ANAVA). The results of these findings indicate: 1) The ability to understand the concepts of students taught with the Cooperative Script Strategy is more influential than taught with the Problem Based Learning Strategy; 2) The mathematical problem solving ability of students taught with Cooperative Script Strategies is no more influential than students taught with Problem Based Learning Strategies; 3) The ability to understand concepts and mathematical problem solving students who are taught with Cooperative Script Strategy is more influential than taught with Problem Based Learning Strategies; 4) There is an interaction between learning strategies with the ability to understand concepts and solve students' mathematical problems.